Karakteristik Keluarga Hindu Di Desa Bayunggede Provinsi Bali - Ni Komang Sutriyanti (Religious: Jurnal Studi Agama-Agama dan Lintas Budaya, 2019)
Humans are individual beings and social beings, who have different personalities and characters from one another. Harmony will determine humans to be able to adjust themselves to their environment. Social and individual life greatly influences human life, such as family, friends, community, and state. The family is the smallest unit in a society consisting of father, mother, and child. The family has an important role in shaping the character of children ranging from in the womb to adulthood. Children are the next generation of the Nation which must be well educated. Harmony in the family will produce children who are of good character and intelligence, so the family is the main factor influencing the formation of a child's character. If the family fails to educate children, the child will have a bad character and will affect the development of the nation's civilization. Bayunggede Village is a tourist village located in Kintamani District, Bangli. The character of the Balinese people in the Bayunggede Village, in general, seems to live full of harmony even though it has been exposed to modernization, they have a uniqueness in the structure of the family organization that forms the character of family harmony.